Evaluating the properties of intrinsic functional brain networks vulnerable to Alzheimer's disease during development through connectomics analysis: Preliminary findings from the PRANK study. (1st February 2022) - Phipps, Connor J.; Sexton, Jennifer N.; Behm, Lillian; DeCesare, Thomas A.; Heller, Abi M.; Maerlender, Arthur C.; Phatak, Vaishali S.; Cramer, Justin A.; Blair, James; Murman, Daniel L.; Warren, David E.
Abstract: Background: The organization of the brain's intrinsic functional networks changes during healthy lifespan development, but pathologies such as Alzheimer's disease (AD) alter the normative trends in functional network organization. Similarly, cognitive abilities such as memory change across the lifespan, but AD pathology causes memory deficits relative to normative expectations. While AD‐related changes in memory and brain networks are often observed in older adults, it is possible that vulnerability to AD is established through differences in early‐life brain and cognitive development including the periadolescent epoch. Here, we used a cross‐sectional approach to study the organization of AD‐vulnerable brain networks and memory in healthy periadolescent children. Data were drawn from the Polygenic Risk of Alzheimer's Disease in Nebraska Kids (PRANK) study. The goal of our research is to evaluate whether early‐life functional brain development may create vulnerabilities to late‐onset AD. Method: To better understand the relationship between network properties of the brain and hippocampal‐dependent memory, we studied cognitive and brain measures in a preliminary sample of periadolescent children (N=40) and healthy young adults (N=10) from the PRANK study. Cognitive assessment included a standardized paired associates learning task (CANTAB), a task that requires hippocampal‐dependent relational memory. Brain structure and function were assessed with MRI protocols adapted from the Human Connectome Project. Resting‐state fMRI data was used to measure resting state functional connectivity which supported our investigation of brain network properties. Analysis focused primarily on the measurement of whole‐brain network properties. Result: We observed differences in brain variables between the PRANK participants and the dataset of healthy young adults. Between‐group differences were observed in modularity scores and other graph theoretical measures of network organization. We also observed relationship between the functional network properties of periadolescent children and their cognitive performance on the CANTAB task. Conclusion: Our ongoing study measures the association of brain variables, cognitive performance, and AD polygenic risk score in periadolescent children. Our preliminary analysis of brain and cognitive measures illustrate functional network properties of the periadolescent brain with a focus on associations with cognitive performance. Future directions include examining the association between AD polygenic risk score and the same network properties.